Pengelolaan Wakaf Tunai di Masjid Al-Munawwarah Kelurahan Penyengat Rendah Kecamatan Telanai Pura Kota Jambi - Arif Mustofa; Maulana Yusuf; Refky Fielnanda (MUQADDIMAH: Jurnal Ekonomi, Manajemen, Akuntansi dan Bisnis, 2023)
The subject matter of this thesis is how cash waqf is managed at the Al-Munawwarah Mosque, Penyengat Rendah Village, Telanai Pura District, Jambi City. The purpose of this discussion is to find out how to manage cash waqf, cash waqf management, and supporting and inhibiting factors in managing cash waqf at the Al-Munawwarah Mosque, Penyengat Low Village, Telanai Pura District, Jambi City. This research is a field research using qualitative methods. Data collection techniques with observation, interviews and documentation. The interviewees consisted of 5 sources, namely Mr. Yatno, Mr. Nana Nuryana, Mr. Syahrul Riyadi, Mr. M. Heri, and brother Abdi. The results of this study are that the management of cash waqf is managed directly by the administrators of the mosque, especially the treasurer. The management of cash waqf is carried out by creating a compensation program for orphans and the poor and community empowerment programs. In the process of managing cash waqf there are supporting factors, namely the enthusiasm of the congregation and residents for cash waqf so that the funds collected every week or month are relatively large, while the inhibiting factors are the lack of human resources in managing cash waqf, especially nazhir and the lack of public awareness of the importance waqf cash.